ChemInform Abstract: Dual Catalysis Sees the Light: Combining Photoredox with Organo‐, Acid, and Transition‐Metal Catalysis. Issue 26 (1st July 2014) - Hopkinson, Matthew N.; Sahoo, Basudev; Li, Jun‐Long; Glorius, Frank
Abstract Review: [61 refs.